Risk assessment, spatial patterns and source apportionment of soil heavy metals in a typical Chinese hickory plantation region of southeastern China - Zhao, Keli; Zhang, Luyao; Dong, Jiaqi; Wu, Jiasen; Ye, Zhengqian; Zhao, Weiming; Ding, Lizhong; Fu, Weijun (Geoderma, 2020)
•Spatial patterns of soil heavy metals in a Chinese hickory plantations region was investigated.•The soils were contaminated by Cd and Cu.•Moran’s I and geostatistics were applied to reveal spatial variation of heavy metals in soils.•The main sources of pollution were related to mining and fertilizer application. Chinese hickory (Carya cathayensis Sarg.) is a famous woody nut in China. Currently, there is an increasing concern related to the soil heavy metal pollution in Chinese hickory plantations. In this study, a total of 188 soil samples were collected from Lin’an city, a typical Chinese hickory production area. The results showed that the average background concentrations of Cd, Cu, Zn, Pb, Ni and Cr in soils were 0.37, 40.76, 87.61, 30.10, 28.33 and 56.57 mg kg−1, respectively. The Cd and Pb concentrations in Chinese hickory plantation soils had strong variability coefficients of 186.49% and 95.42%, respectively. Compared with the background values in Zhejiang province, the heavy metals were enriched in the plantation soils. The accumulation ratio followed the order of Cu > Cd > Pb > Ni > Zn > Cr. Part of the study area was seriously contaminated by Cd and Cu, as 31.38% of soil Cd and Cu samples exceeded the second grade standardized value of Environmental Quality Standards of Soils (EQSS). The soils in our study area generally reached a moderate ecological risk, as its average RI value reached 103. Moran’s I and Kriging interpolation results revealed that all the studied heavy metals in soils had clear spatial distribution patterns. The high values of soil heavy metals (except Pb) were mainly distributed in the localities closest to the mine area. The apportionment of heavy metal pollution sources showed that the Cu, Ni and Cr in soils were mainly related to mining activities, Pb was closely related to fertilizer application, Cd and Zn were related to both. The heavy metals in soils may pose a potential threat to local ecosystem and human health. Our results implied that soil heavy metals should be tested, and risk-based management should be performed in the economic plantations in China. These maps could provide useful information for forestry and environmental management.